Development of facies and C/O-isotopes in transects through the Ludlow of Gotland: Evidence for global and local influences on a shallow-marine environment - Samtleben, Christian; Munnecke, Axel; Bickert, Torsten (Facies, 2000)
The Silurian of Gotland is characterized by repeated changes in depositional facies development. The deposition of uniform sequences of micritic limestones and marls was interrupted four times by the growth of reef complexes and the formation of expanded carbonate platforms. Coinciding with these, often abrupt, facies changes extinction events occurred which predominantly affected nektonic and planktonic organisms. Ratios of carbon- and oxygen-isotopes covary with the facies development. Periods in which the deposition of limestonemarl alternations prevailed are characterized by relatively low C- and O-isotope values. During periods of enhanced reef growth isotope values are high. For these changes, Bickert et al. (1997) assume climatic changes between humid "H-periods", with estuarine circulation systems and cutrophic surface waters with decreased salinity in marginal seas, and arid "A-periods", with an antiestuarine circulation and oligotrophic, stronger saline surface waters. In order to separate local and regional influences on the isotopic development from the global trend, the interactions between facies formation and isotope record have to be clarified. For this purpose, the patterns of isotope values in the upper part of the Silurian sequence on Gotland (upper Wenlock -upper Ludlow) has been determined and stratigraphically correlated along four transects through different facies areas. Facies formation during this time interval was investigated by differentiation and mapping of twelve facies complexes in the southern part of Gotland. These include shelf areas, reef complexes with patch reefs and biostromes, backreef facies, and marginal-marine deposits. The good correspondence between the carbon-isotope records of the four transects suggests that local environmental conditions in the different facies areas did not influence the δC values. Therefore, a supra-regional or even global mechanism for the C-isotope variations is likely. In contrast to carbon istopes, the oxygen-isotope values of the four transects generally show parallel trends, but higher variabilities and in parts distinctly deviating developments with a trend to more negative values. These are interpreted as an effect of local warming in small shallow-water areas which developed during arid periods in reef complexes and backreef areas. The boundaries between A-periods and H-periods, as defined by δC values, which are interpreted as isochrones, can be mapped. From the upper Homerian to the Pridolian six parastratigraphic isotope zones are defined which only partly match the stratigraphic division of Hede (1942, 1960). The isotope stratigraphy results in an improved correlation between the shallow and marginal-marine areas in the eastern part of Gotland and the uniform shelf areas at the west coast of the island. Furthermore, a detailed relationship between the development of carbon and oxygen isotope ratios, the carbonate facies formation, and the succession of palaeontological events could be observed. At the transition from H-periods to A-periods, major extinction events occurred prior to the first increase of δC and δO values. Extinction events affected conodonts, graptolites, acritarchs, chitinozoans, and vertebrates and resulted in impoverished nektonic and planktonic communities. The reef-building benthos was less affected. Parallel to a first slight increase of isotope values, facies began to change, and reefs developed in suitable locations. The subsequent rapid increase of C- and O-isotope values occurred contemporarily with strong facies changes and a short-term drop of sea-level. Oligotrophic conditions in the later stages of A-periods led to strong reef growth and to an expansion of carbonate platforms. The transitions from A-periods to H-periods were more gradual. The δC values decreased slowly, but reef growth continued. Later the reefs retreated and were covered by the prograding depositional facies of shelf areas. The diversity of planktonic and nektonic communities increased again. The close relationship between facies formation, palaeontological events and isotope records in the Silurian suggests common steering mechanisms but gives no indication of the causes for the repeated extincion events related to H-period/A-period transitions. Especially the observation, that strong extinctions occurred prior to changes of isotope values and facies, points to causes that left no signals in the geological record. Hypothetical causes like collapse of trophical nets, anoxias, or cooling events are not evident in the sediment record or do not fit into the regular succession of period transitions. © 2000 Institut für Paläontologie, Universität Erlange
Keywords: Facies Development; Gotland; Palaeoceanography; Silurian (Ludlow); Stable Isotopes; Stratigraphy